Interval models of nonequilibrium physicochemical processes - Morozov, Alexander Yu; Reviznikov, Dmitry L.; Gidaspov, Vladimir Yu (Discrete and continuous models and applied computational science, 2025)
The paper discusses the application of the adaptive interpolation algorithm to problems of chemical kinetics and gas dynamics with interval uncertainties in reaction rate constants. The values of the functions describing the reaction rate may differ considerably if they have been obtained by different researchers. The difference may reach tens or hundreds of times. Interval uncertainties are proposed to account for these differences in models. Such problems with interval parameters are solved using the previously developed adaptive interpolation algorithm. On the example of modelling the combustion of a hydrogen-oxygen mixture, the effect of uncertainties on the reaction process is demonstrated. One-dimensional nonequilibrium flow in a rocket engine nozzle with different nozzle shapes, including a nozzle with two constrictions, in which a standing detonation wave can arise, is simulated. A numerical study of the effect of uncertainties on the structure of the detonation wave, as well as on steadyystate flow parameters, such as the ignition delay time and the concentration of harmful substances at the nozzle exit, is performed.